Fédéralisme, question linguistique et citoyenneté aux Etats-Unis dans le contexte des Amériques - James Cohen (Nuevo mundo - Mundos Nuevos, 2008)
In the U.S. there is neither consensus nor national policy regarding the linguistic issue, whether it concerns the status of English or the languages of minority groups, like Spanish.  The inconsistency of the various policies seems to derive directly from the federal system; it also affects the rights of linguistic minorities and the definition of citizenship. The article examines what a truly democratic policy of recognition of minority languages through bilingual programs for instance involves, and contemplates what a redefinition of a truly republican and even transnational citizenship extended to the Americas entails